Trading co-movements information between credit default swaps, equities and equity options - Nicodeau, Pierre (2022)
The equity, equity derivatives and the credit derivatives markets are linked through some fundamental relationships and their respective prices co-move by reacting to company specific news. Whereas the markets have different pricing assumptions and methodologies, we will prove that they co-move in systematic patterns and we will try to benefit from the latter movement relationships with a trading strategy. Our goal in this research is to estimate if the assets’ relationship has been broken, allowing us to implement an investment strategy based on statistic signals. We believe that the co-movements can be irrational and that different markets can react differently to the same information set, which competes with the efficient market principle.